PERBAIKAN PERILAKU KUAT TEKAN BETON AIR RAWA DENGAN METODE PENYARINGAN AIR - Elhusna Elhusna; Agustin Gunawan (Inersia: Jurnal Teknik Sipil, 2019)
Concrete building construction is easier and more economical when using local material including the water. This article is about improving swamp water by filtering it to use in concrete production. As the comparator is concrete with drinking water from The local water supply utility (PDAM) of Bengkulu. The 15 cm cubes specimens were tested at the age of 7, 14, 21, and 28 days to find out the compressive strength at different ages. The concrete was designed with water cement ratio 0.5, slump value 6-10 cm and maximum aggregate 20 mm. The casting and curing specimens were done according to SNI 03-2493-2002. The compressive strength results showed that the filtered swamp water concrete and the unfiltered one at 28th day were 98,2% dan 90,1% to the PDAM one. The trend of the compressive strength of swamp water concrete tend to decline with the increasing age. The compressive strength of swamp water concrete at age of 28th day was 89,1% lower than the strength at the age of 7th day. The filterred swamp water made the concrete compressive strength better.